DCEUS‐based multiparametric perfusion imaging using pulse‐inversion Bubblet decorrelation. Issue 6 (16th April 2018) - Wang, Diya; Su, Zhe; Zhang, Yu; Zhao, Xiaoyan; Wang, Supin; Wan, Mingxi
Abstract : Purpose: This study aimed to clarify the influences of composite dynamic contrast‐enhanced ultrasound (DCEUS) on multiparametric perfusion imaging (PPI) and to develop a novel PPI scheme through pulse‐inversion Bubblet decorrelation (PIBD) to improve its contrast and detailed discriminability. Method: In in vivo perfusion experiments on rabbit kidneys, a pair of phase‐inverted "Bubblets" was constructed. Phase‐inverted raw radiofrequency echoes were reconstructed by using the maximum coefficients obtained from Bubblet decorrelation analysis and summed to form DCEUS loops. Nine perfusion parameters were estimated from these loops and color coded to create the corresponding PIBD‐based PPIs. Results: In addition to time‐related PPIs, the contrast and detailed discriminability quantified by the average contrast and information entropy of intensity‐ and ratio‐related PPIs were proportional to the microbubble detection sensitivity and microvascular discriminability evaluated by CTR in DCEUS techniques. Compared with the second harmonic, the CTR of DCEUS and the average contrast and information entropy of PPI were significantly improved by 9.03 ± 5.39 dB ( P  < 0.01), 6.39 ± 1.38 dB ( P  < 0.01), and 0.57 ± 0.15 ( P  < 0.05) in PIBD technique, respectively. Conclusions: As a multiparametric functional imaging technique, these improvements in the proposed scheme can be beneficial to accurately quantify and depict the hemodynamic perfusion features and details of tumor angiogenesis, and further can also assist clinicians in making a confirmed diagnosis.